Occupational co-exposure to solvents: the case of styrene and xylene - Meneses, Márcia (2018)
Although the health effects of single contaminants may be apparent under circumstances of high exposure, the great majority of people are exposed to several chemicals simultaneously. Exposure to mixtures or co-exposure to several substances is the common feature in occupational settings. Organic solvents are widely employed in industry and are used in large quantities across the world. Occupational exposure to xylene and styrene is usual in several industries as raw materials in the production of paints, pigments, and glues. Both substances have effects in the central nervous system and due to this, we might consider that simultaneous exposure can create a higher risk than that of a single substance due to possible interactive effects.